Photocatalytic degradation of Ofloxacin using Bare BiVO4 - Dhiman, Ishita (My University, 2024)
Presently, the most pressing issue is meeting the need for clean and pure water. Several difficulties have come up that impede the availability of this essential resource. In view of foregoing problem, various techniques such as adsorption, coagulation, photocatalytic degradation, and biological methods were executed for treating the toxic pollutants from wastewater. Photocatalytic degradation is enormously effective advanced oxidation process used for the dismissal of noxious pollutants. Considering it, the photocatalyst BiVO4 was prepared from hydrothermal method, which then employed for the degradation of ofloxacin. Ofloxacin is fluoroquinolone antibiotic, popular in practices of anti-infective therapy and used to address various bacterial ailment The photocatalyst have been characterised by XRD, FESEM, DRS, DLS and ZETA. The FESEM reveals that BiVO4 having an irregular worm-like shape and an average particle size of 240 nm. The photocatalyst shows its maximum degradation efficiency of 72 % in 120 min in neutral medium when irradiated with visible light. Degradation studies in acidic and basic medium has similarly been noted. The reactive species participated in the photocatalytic process were superoxide and hydroxyl radicals. As a results, BiVO4 has a potential of a photocatalyst for effectively degradation of ofloxacin attribute to its high stability and environment friendly synthesis.
Keywords: Photocatalysis; Wastewater Treatmaent; Emerging Contaminants; Nanomaterials